Findings of Fahr’s Syndrome in A Patient Suspected With Subarachnoid Hemorrhage: An Evidence-Based Case Report - Gilbert Sterling Octavius; Theo Audi Yanto; Nicholas Gabriel H.R.; Eka Julianta Wahjoepramono; Harsan (Talenta Publisher, 2020)
ABSTRACT Fahr’s syndrome is an entity where there is symmetrical bilateral calcification of basal ganglia with parkinsonian and psychiatric symptoms. However, due to its rarity, clinicians tend not to include Fahr’s syndrome in their differential diagnosis. This article aims to raise awareness about the diagnosis of Fahr’s Syndrome through its unique presentation in this patient. Data was obtained primarily and secondarily. In this case, a 32 years old male was referred to our clinic with chief complaints of headache since a week prior and a seizure 5 days ago. A head CT and a CT angiography (CTA) of the circulus willisi were done and a bilateral and symmetrical calcification of the corona radiata, basal ganglia, thalamus, and nucleus dentatus were found. There is also hypocalcemia and low Parathyroid Hormone (PTH). Fahr’s Syndrome may manifest unusually and hence clinicians have to be aware of diagnosing this entity. Keywords: Fahr’s Disease, Fahr’s Syndrome ABSTRAK Sindroma Fahr’s merupakan sebuah penyakit yang ditandai dengan kalsifikasi bilateral sietris dari basal ganglia dengan gejala psikatri dan parkinsonisme. Namun, akibat jarangnya ditemukan penyakit ini, klinisi cenderung tidak memikirkan sindroma Fahr’s sebagai salah satu diagnosis banding. Artikel ini bertujuan untuk meningkatkan kewaspadaan terhadap diagnosis Sindroma Fahr’s melalui presentasi unik pada pasien ini. Data diambil secara primer dan sekunder. Pada kasus ini, seorang laki-laki berusia 32 tahun dirujuk dengan keluhan utama sakit kepala sejak satu minggu dan kejang 5 hari sebelum masuk rumah sakit. Computed Tomography (CT) scan kepala dan Computed Tomography Angiography (CTA) dari sirkulus willisi dilakukan dan ditemukan adanya kalsifikasi bilateral simetris pada korona radiata, basal ganglia, talamus dan nukleus dentatus. Pada pemeriksaan laboratorium ditemukan adanya hipokalsemia dan hormon paratiroid (PTH) yang rendah. Sindroma Fahr’s dapat datang dengan presentasi yang tidak khas sehingga para klinisi harus lebih tajam dalam mendiagnosis kasus ini. Kata kunci: Penyakit Fahr’s, Sindroma Fahr’s